A prospective population-based cohort study of the prevalence, incidence and impact of obsessive-compulsive symptomatology. (August 2013) - Fineberg, Naomi A.; Hengartner, Michael P.; Bergbaum, Carmel E.; Gale, Tim M.; Gamma, Alex; Ajdacic-Gross, Vladeta; Rössler, Wulf; Angst, Jules
Abstract: Objective. Prospective longitudinal studies of obsessive-compulsive disorder (OCD) and sub-diagnostic obsessive-compulsive symptomatology in the non-clinical population, using age-defined cohorts, are rare. This study aimed to investigate the effect of OC symptoms on distress and psychosocial function and the effect of early-onset OC symptoms. Methods. 591 subjects drawn from the general population of Zurich, Switzerland were interviewed seven times between 1979 (at age 20/21) and 2008 (age 49/50). Data for socio-demographic variables and psychosocial impairment was also collected and compared with a control-group without OC symptoms drawn from the same population. Results. The unweighted cumulative one-year rate of OCD in this sample was 5.1% and 21.7% reported some degree of clinically-relevant OC symptomatology (OCD or OCS). OCD appeared more prevalent in females whereas OCS and OC symptoms were more prevalent in males. The weighted cumulative prevalence rates, representative of the general population, for OCD, OCS and OC symptoms were 3.5%, 9.7%, and 11.2%, respectively. We could not identify OCD occurring before the age of 10 years, though sub-threshold cases were reported as early as age 2 years, whereas by the age of 22 years, around two thirds of OCD cases had emerged and no new cases developed OCD after around 37 years. Males were statistically significantly younger than females at onset of any OC symptomatology. Conclusions. Clinically-relevant OC syndromes start early and are associated with substantial distress, treatment-seeking activity and in the case of OCD, functional disability.